Perancangan Sistem Persediaan Barang Habis Pakai Di Politeknik Jambi - Rezagi Meilano; Ega Wira Pengestu; Ikbal Ramadani (Journal of Applied Accounting and Business, 2021)
Inventories can be interpreted as goods that are stored and used or sold in the future or period to come. Inventory must be determined first before the sale is made so that the company must determine the optimal amount of merchandise inventory so that the number of purchases can reach the minimum purchase amount. To achieve the effectiveness of modern inventory supplies, universities or colleges must make changes that can encourage activity towards inventory and cost efficiency. The purpose of this study is to analyze the total cost of inventory and make it easier to record inventory using a web-based application in PHP, and a MySQL database.